Pergeseran Orientasi Sistem Pemilu Proporsional Terbuka dalam Praktik Penyelenggaraan Pemilu Legislatif - Adolof Seleky; Eivandro Wattimury (CV. ULIL ALBAB CORP, 2023)
Elections are a means of exercising popular sovereignty guaranteed in the constitution. Constitutionally, the legislative election system adopted by Indonesia is a proportional representation system variant of the